Performance and lifetime simulation of ion thruster optics - Farnell, Cody Coffman, author; Williams, John D., advisor; Wilbur, Paul J., advisor (Colorado State University. Libraries, 2007)
A simulation code, ffx, was developed to study various aspects of ion thruster optics. Information concerning sheaths, impingement limits, perveance, electric potential, charge exchange, and sputtering is covered. Electron backstreaming and pit and groove wear are discussed in detail as two grid failure mechanisms. The code was used to study the effects of several parameters on grid performance and lifetime, including grid spacing, aperture diameter, and grid thickness. An evolutionary algorithm was used with the ffx code to design grid sets, utilizing net accelerating voltage and current density as primary input parameters. Validation of the ffx code was accomplished through comparison to other ion optics codes and to experimental data obtained from both gridlet and full thruster testing. Gridlet test comparisons included simulations of finite aperture grid sets. The NSTAR thruster was studied in detail with regard to lifetime. The methods used for accurate and efficient optics simulation are discussed, including the multigrid method for solving for electric potential.
Keywords: electric propulsion; ion thruster optics; aerospace materials; mechanical engineering; aerospace engineering